2016
DOI: 10.1007/s00394-016-1230-0
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa polyphenols and fiber modify colonic gene expression in rats

Abstract: Purpose Cocoa intake has been associated with health benefits, improving cardiovascular function and metabolism, as well as modulating intestinal immune function. The aim of this study was to take an in-depth look into the mechanisms affected by the cocoa intake by evaluating the colonic gene expression after nutritional intervention, and to ascertain the role of the fiber of cocoa in these effects.MethodsTo achieve this, Wistar rats were fed for 3 weeks with either a reference diet, a diet containing 10 % coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
3
11
0
Order By: Relevance
“…These changes, together with the lower urinary excretion of acetone, suggest an alteration in energy metabolism through the modulation of ketogenesis, BCAA metabolism and the TCA cycle. This shift in energy strategy, together with the lower expression of genes involved in lipid metabolism (33) , may contribute to the reduction of body weight in C10-fed rats, reported here and in previous studies (23,26,28) . Changes in NAD + pathway metabolism further support an alteration in energy metabolism.…”
Section: Discussionsupporting
confidence: 73%
“…These changes, together with the lower urinary excretion of acetone, suggest an alteration in energy metabolism through the modulation of ketogenesis, BCAA metabolism and the TCA cycle. This shift in energy strategy, together with the lower expression of genes involved in lipid metabolism (33) , may contribute to the reduction of body weight in C10-fed rats, reported here and in previous studies (23,26,28) . Changes in NAD + pathway metabolism further support an alteration in energy metabolism.…”
Section: Discussionsupporting
confidence: 73%
“…In this line, it has been recently reported that most of the beneficial effects attributed to cocoa are not only due to its fibre content, and polyphenols and other compounds could also be key factors. 52 Thus, epicatechin and procyanidins seem to contribute in the maintenance of renal function and structure during diabetes. 17,33,35,42 In addition, theobromine alone can protect against uric acid crystallization, 53 and in combination with cocoa flavanols enhance their protective vascular effects, 54 which also seem to participate in the preservation of kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…B cells are responsible for the regulation of commensal bacteria producing IgA [ 52 ], so the more relative abundance of Proteobacteria could activate B cells for IgA production, evidencing higher levels of these mucosal antibodies. Previous studies have associated the effect of a 10% cocoa diet on the reduction of IgA with gene expression modifications of several genes involved in the differentiation and maturation of B cells [ 53 , 54 ]. In this sense, IL-6 gene expression is reduced by the cocoa diet [ 53 ], which could reflect a lower IL-6 secretion by dendritic cells, thus partially explaining the possible dendritic cell involvement in that process.…”
Section: Discussionmentioning
confidence: 99%